Effect of Heatsink Material on the Efficiency of Solar Panel-Thermoelectric Hybrid Devices - Fitriana, Fitriana; Kurniawan, Dani Rizky; Wijaya, Muhammad Antoni; Auliq, Muhammad A’an (ELKHA : Jurnal Teknik Elektro, 2024)
Solar panels exposed to solar radiation will produce heat, affecting their efficiency. A solution to this problem is integrating solar panels with thermoelectric generators that can convert thermal energy into electrical energy. In general, thermoelectric generators are equipped with heatsinks as heat absorbers. Many studies only look at the addition of heatsinks without examining the effect of the type of heatsink material used. Based on this background, this study identifies the effect of heatsink materials on the efficiency produced by solar panel thermoelectric devices. The purpose of this study is to determine which heatsink material can produce high efficiency in solar panel-thermoelectric devices. This research is useful for improving the efficiency of solar-thermoelectric hybrid devices. The novelty of this study is the selection of various heatsink materials that are directly tested against the efficiency of hybrid devices. The heatsink materials tested in this study were aluminum and copper. The equipment was tested by measuring the current and voltage generated by the solar panel-thermoelectric using a multimeter which was then used to calculate its power. The results showed that the hybrid solar panel-thermoelectric device with a heatsink made of copper produced a higher output power of 1.882 mW compared to aluminum material which was only 0.513 mW.